2018
DOI: 10.1039/c8ta04224a
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the NaxMoO2phase diagram for low sodium contents (x≤ 0.5)

Abstract: Phase diagram in the NaxMoO2system (x≤ 0.5) determined using electrochemistry andin situX-ray powder diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As part of the investigation of the Na x MoO 2 system, a well-crystallized pristine material Na 2/3 MoO 2 has been synthesized by solid state synthesis. The sodium electrochemical intercalation or deintercalation in a sodium battery made with this material as the positive electrode has been used as a powerful technique to explore the phase diagram in the NaMoO 2 –MoO 2 system. ,, More specifically, our in situ X-ray diffraction experiment performed during sodium electrochemical intercalation showed that a composition close to Na 1 MoO 2 existed at very low voltage (<1 V vs Na + /Na) . Nevertheless, the organic liquid electrolyte (NaPF 6 in propylene carbonate) was not stable at this low voltage, and it decomposed before all the Na x MoO 2 ( x ≈ 0.9) phase could be transformed into NaMoO 2 , making the electrochemical method not adequate for NaMoO 2 preparation.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…As part of the investigation of the Na x MoO 2 system, a well-crystallized pristine material Na 2/3 MoO 2 has been synthesized by solid state synthesis. The sodium electrochemical intercalation or deintercalation in a sodium battery made with this material as the positive electrode has been used as a powerful technique to explore the phase diagram in the NaMoO 2 –MoO 2 system. ,, More specifically, our in situ X-ray diffraction experiment performed during sodium electrochemical intercalation showed that a composition close to Na 1 MoO 2 existed at very low voltage (<1 V vs Na + /Na) . Nevertheless, the organic liquid electrolyte (NaPF 6 in propylene carbonate) was not stable at this low voltage, and it decomposed before all the Na x MoO 2 ( x ≈ 0.9) phase could be transformed into NaMoO 2 , making the electrochemical method not adequate for NaMoO 2 preparation.…”
Section: Resultsmentioning
confidence: 91%
“…Among these phases, the structure has only been reported for Na 1/2 MoO 2 from single crystal X-ray diffraction and a specific arrangement of short Mo–Mo bonds (2.53 Å) in zigzag chains separated from each other by long Mo–Mo distances (3.20 Å) has been found . We have recently investigated the sodium electrochemical (de)­intercalation in the Na 2/3 MoO 2 phase, and we have reported the existence of 16 single phases in the composition range 0.3 ≤ x < 1. , The very small difference in composition and the reversibility of the (de)­intercalation process suggest that these phases do not only differ from one another in the sodium patterning but also in the molybdenum clustering. Even though we could not solve any of their complex structures, one can expect to find molybdenum clusters within the [MoO 2 ] layers, given the rich chemistry of molybdenum clusters observed in sulfurs, selenides, halogens, and oxides. The fully intercalated phase, NaMoO 2 , was the subject of a sole scientific paper 50 years ago reporting on its synthesis from the reaction of metal sodium on MoO 2 at 400 °C under a vacuum .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The layered NaxTMO2 (TM=transition metal) are considered to be the most promising cathodes. [7][8][9][10][11][12][13][14][15][16][17][18] However, they suffer from severe capacity decay mainly caused by the undesired phase transition stemming from the large size of sodium. [19][20][21] Thus, the structural stability is an important issue for developing large capacity and high reversible cathodes.…”
mentioning
confidence: 99%